Case Report: Generalized anxiety disorder and hypertension: a bidirectional loop unraveled by integrated management - Chen, Junming; Yang, Yuxing; Jiang, Fugui (Frontiers in Psychiatry, 2025)
BackgroundGeneralized anxiety disorder (GAD) and hypertension (HTN) exhibit a clinically significant bidirectional relationship characterized by neuroendocrine dysregulation and autonomic dysfunction. Their comorbidity presents diagnostic and therapeutic challenges due to overlapping symptoms and fragmented care pathways.Case presentationWe report a 61-year-old male with 26-year refractory HTN and new-onset GAD triggered post-thyroidectomy. Despite triple antihypertensive therapy (nifedipine, arotinolol, sacubitril/valsartan), blood pressure (BP) remained uncontrolled (176/105 mmHg) with severe anxiety (HAMA = 36). Secondary HTN investigations were negative. Multimodal management combining pharmacotherapy (escitalopram, tandospirone), transcranial magnetic stimulation (9 sessions), biofeedback (14 sessions), psychotherapy, and lifestyle interventions achieve: mean BP decreased significantly from 176/105 mmHg to 125/72 mmHg during hospitalization; significant anxiety reduction (HAMA = 3), mean BP stabilized at 131/77 mmHg with 50% reduction in antihypertensive dosages, normalization of elevated ACTH (99.9→normal pg/mL) and cortisol (18.7→normal μg/dL) and sustained improvement at 6-month follow-up.ConclusionThis case demonstrates thyroidectomy-induced endocrine disruption as a novel trigger in the GAD-HT bidirectional loop. Multimodal therapy targeting shared neurobiological pathways (HPA axis, autonomic regulation, serotonin signaling) effectively breaks this cycle, underscoring the imperative for integrated mental-cardiovascular care in treatment-resistant cases.